2018
DOI: 10.3390/min8040132
|View full text |Cite
|
Sign up to set email alerts
|

Surface Chemical Characterisation of Pyrite Exposed to Acidithiobacillus ferrooxidans and Associated Extracellular Polymeric Substances

Abstract: A. ferrooxidans and their metabolic products have previously been explored as a viable alternative depressant of pyrite for froth flotation; however, the mechanism by which separation is achieved is not completely understood. Scanning electron microscopy (SEM), photoemission electron microscopy (PEEM), time-of-flight secondary ion mass spectrometry (ToF-SIMS) and captive bubble contact angle measurements have been used to examine the surface physicochemical properties of pyrite upon exposure to A. ferrooxidans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 86 publications
0
8
0
Order By: Relevance
“…This enabled the selective separation of sphalerite, galena and quartz from pyrite and chalcopyrite after prior treatment with bacterial proteins. In the study of La Vars et al [26], EPS was detected within 2 h of contact with Acidithiobacillus ferrooxidans on pyrite surface rendering the surface hydrophilic. Acidithiobacillus ferrooxidans produced polysaccharides and fatty acid compounds in the initial adhesion stage, and only later hydrophobic protein-and nucleic acid-rich EPS.…”
Section: Attachment Of Microorganisms On Mineral Surfacementioning
confidence: 95%
See 3 more Smart Citations
“…This enabled the selective separation of sphalerite, galena and quartz from pyrite and chalcopyrite after prior treatment with bacterial proteins. In the study of La Vars et al [26], EPS was detected within 2 h of contact with Acidithiobacillus ferrooxidans on pyrite surface rendering the surface hydrophilic. Acidithiobacillus ferrooxidans produced polysaccharides and fatty acid compounds in the initial adhesion stage, and only later hydrophobic protein-and nucleic acid-rich EPS.…”
Section: Attachment Of Microorganisms On Mineral Surfacementioning
confidence: 95%
“…The quantity of microorganisms needs to be high for efficient bioflotation to compete with conventional flotation chemicals [22]. La Vars et al [26] showed that mineral surface is modified already by low cell coverage.…”
Section: Bioflotation and Flocculationmentioning
confidence: 99%
See 2 more Smart Citations
“…This study, therefore, also points to the need for a better integration of biogeochemical cycles of precious metals with other large biogeochemical cycles, e.g., those of carbon, nitrogen and sulfur. In their application-driven study, La Vars et al [14] achieve this by assessing Acidithiobacillus ferrooxidans and its associated extracellular polymeric substances (EPS). This bacterium forms biofilms on the surface of gold-bearing sulfide mineral pyrite and the resulting EPS may be a viable alternative depressant of pyrite for froth flotation.…”
mentioning
confidence: 99%